Gender Portrayal of English Textbooks in A State Islamic Junior High School In Gowa Regency, South Sulawesi, Indonesia - Siti Azisah (Universitas Islam Negeri Alauddin Makassar, 2016)
Indonesia has adopted gender equality policy by issuing a number of law including Gender Mainstreaming policy issued by the President Abdurrahman Wahid with the Presidential Instruction No. 9 year 2000. This policy was already issued 16 years ago. This paper aimed to examine the influence of gender mainstreaming policy on the textbooks used in Indonesian education as well examines the teachers’ perspectives on gender roles. Several research questions were posed: Did the policy influence the gender portrayals of the English textbooks used by teachers in State Islamic Junior High School? Was any change in gender portrayals reflected in the English textbooks for all classes? In analysing textbooks. I used the content analysis with the following categories: visibility (visible or invisible); equity (balance or imbalance); stereotyped or non-stereotyped; neutral or gender based; progressive or non-progressive. The research uncover that gender mainstreaming policy has big influence on English textbooks used by the teachers in a state Islamic junior high school.